2023
DOI: 10.3390/ijms24076518
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Processes in Alzheimer’s Disease—Pathomechanism, Diagnosis and Treatment: A Review

Abstract: Alzheimer’s disease is one of the most commonly diagnosed cases of senile dementia in the world. It is an incurable process, most often leading to death. This disease is multifactorial, and one factor of this is inflammation. Numerous mediators secreted by inflammatory cells can cause neuronal degeneration. Neuritis may coexist with other mechanisms of Alzheimer’s disease, contributing to disease progression, and may also directly underlie AD. Although much has been established about the inflammatory processes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(16 citation statements)
references
References 231 publications
1
7
0
Order By: Relevance
“…A considerable body of evidence suggests that many neurological and psychiatric disorders are accompanied by disorders of IMs, like interleukin (IL)-1b, IL-2, IL-6, interferon (IFN), tumor necrosis factor a (TNF a), the soluble IL-6 receptor (sIL-6R), and the IL-1 receptor antagonist (IL-1RA). These disorders include DD [ 135 , 136 , 137 , 138 , 139 , 140 ], ALS [ 141 ], AD [ 142 , 143 , 144 ], HE [ 145 , 146 ], etc. It has been suggested that pro-inflammatory cytokines can induce stress-induced neuroendocrine and central neurotransmitter changes similar to those in patients with depression [ 147 ], and IFN-a immunotherapy has been shown to induce depression [ 148 , 149 ].…”
Section: Resultsmentioning
confidence: 99%
“…A considerable body of evidence suggests that many neurological and psychiatric disorders are accompanied by disorders of IMs, like interleukin (IL)-1b, IL-2, IL-6, interferon (IFN), tumor necrosis factor a (TNF a), the soluble IL-6 receptor (sIL-6R), and the IL-1 receptor antagonist (IL-1RA). These disorders include DD [ 135 , 136 , 137 , 138 , 139 , 140 ], ALS [ 141 ], AD [ 142 , 143 , 144 ], HE [ 145 , 146 ], etc. It has been suggested that pro-inflammatory cytokines can induce stress-induced neuroendocrine and central neurotransmitter changes similar to those in patients with depression [ 147 ], and IFN-a immunotherapy has been shown to induce depression [ 148 , 149 ].…”
Section: Resultsmentioning
confidence: 99%
“…50 However, the in ammatory process in AD certainly involves several proin ammatory factors, such as cytokines (e.g., IL-6, TNF-α), transcription factors (e.g., NF-κB), and enzymes (e.g., COX-2). 51 Experimental studies have shown that β-sitosterol can induce anti-neuro injury effects by inhibiting COX-2, IL-6, and NO. 52 Tau proteins are phosphorylated proteins found in the normal human brain.…”
Section: Discussionmentioning
confidence: 99%
“…Study suggested that berberine promoted autophagic clearance of tau protein by enhancing autophagic activity, thereby reducing Aβ production and the resulting neuronal apoptosis ( Chen et al, 2020 ). Acetylcholine (ACh), one of the major neurotransmitters in the brain ( Twarowski and Herbet, 2023 ), plays an crucial role in maintaining learning and memory capacity ( Hampel et al, 2017 ). In the process of aging and neuronal degeneration, the cholinergic system undergoes severe lesions, mainly manifested as the reduction of ACh synthesis, release and uptake in the brain, which is closely related to the severity of dementia ( Kim et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%